ANALISIS KUALITAS AIR TANAH DANGKAL DAN KEBUTUHAN AIR PADA KAWASAN PESISIR LEATO UTARA - Irana I. Koem Ibrahim Ismail; Aryati Alitu; Marike Mahmud (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2026)
Leato Utara, located in Gorontalo City, Gorontalo Province, is a coastal area known as a tourist destination and residential centre. The increasing population in this area has led to a growing demand for clean water. As a result, most residents rely on shallow aimed to analyse the quality of groundwater in Leato Utara and asses the community’s water demand. The analysis method involved testing physical parameters (TDS, turbidity, temperature, colour, odour, and salinity), chemical parameters (iron, pH, manganese, and hardness), and microbiological parameters (Escherichia coli and Coliform) based on the Ministry of Health Regulation No. 2 of 2023. Water demand was analysed based on population data, including domestik and non-domestik water needs, water losses, and total water demand. The results indicated that shallow groundwater quality in Leato Utara varies across physical, chemical, and microbiological parameters, Physical parameters such as turbidity, temperature, colour, and salinity met the quality standards 100%, but only 33.33% of TDS samples met the standard. Chemical parameters such as pH, manganese, and iron fully met the standards, while only 33.33% of hardness results were within acceptable limits. Microbiological tests revealed that 66.67% of samples exceeded the standard for Coliform and 33.33% for E. Coli, indicating potential bacterial contamination. Water availability was found to be 28.512 liters/day, which is insufficient compared to the community’s total demand of 34.008 liters/day. Therefore, appropriate measures are needed to address this water supply issue.